Author-Activism: Philosophy of Dissent in the Writings of Arundhati Roy - Mody, Ohio State University, USA, Naman; Rath, Indian Institute of Technology, Gandhinagar, India, Arnapurna (Asiatic: IIUM Journal of English Language and Literature, 2013)
In this paper our analysis focuses on theorising â€œdissentâ€ as a philosophical-politicalÂ â€œmomentâ€ and studying the voice of â€œdissentâ€ through the writings of Arundhati Roy. We argue through a close reading of Royâ€™s texts that dissent is intrinsic to humanÂ thoughts and dialogues. Taking our cue from Robert Barskyâ€™s study of Noam Chomskyâ€™s life as a â€œlife of dissentâ€ and from Brian Martinâ€™s paper â€œAdvice for theÂ Dissident Scholar,â€ in Thought and Action, Vol. 14, we argue that the term dissent is set in a complex interplay of multiple subjectivities. A dissenting voice is looked upon as a voice that goes against, rather than with the established norms of the society, and in extreme cases, is fiercely opposed. Taking these theoretical premises further into apraxical mode, we analyse Arundhati Royâ€™s non-fictional works, and bring out the element of dissent, which is implicitly present in each of her essays. Royâ€™s dissent, mainly political in nature, usually takes the form of scathing criticism â€“ the expressionÂ of which is fearless and forthright. Our interpretation of Royâ€™s works is in connectionÂ with the impact and the substantiality of her dissent.